Recycling and processing technology for spinning regenerated fibers from waste polyester textiles

By crushing, pretreating, semi-melt densification, alcoholylation reaction and composite nucleation system for waste polyester textiles, modified alcoholylation monomers were prepared and regenerated through twin-screw extruder and melt spinning mechanism. Fiber solves the problems of insufficient fiber stacking density, heat resistance and mechanical strength in the prior art, and achieves the improvement of the performance of recycled fibers.

CN119411243AInactive Publication Date: 2025-02-11JIESHOU TIANZHU TEXTILE MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411552099.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the fiber stacking density, heat resistance and mechanical strength prepared by recycling and regeneration of waste polyester need to be further improved.

Method used

By crushing, pretreating, semi-melt densification, alcoholylation reaction and composite nucleation system, modified alcoholylation monomers were prepared and regenerated through twin-screw extruder and melt spinning mechanisms. fiber.

Benefits of technology

The bulk density, thermal stability and mechanical strength of the recycled fibers are improved, and their viscosity, crystallization ability and flame retardant properties are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005115357290000111
    Figure BDA0005115357290000111
Patent Text Reader

Abstract

The invention discloses a recycling and processing technology for spinning regenerated fibers from waste polyester textiles, and belongs to the technical field of waste polyester regeneration. According to the recycling and processing technology, the waste polyester textiles are subjected to semi-melt extrusion densification pretreatment by adopting a semi-degradation tackifying technology, and EG which enables the waste polyester textiles to be incompletely degraded is added; the regenerated polyester fiber prepared by the method has the advantages that the high-added-value regenerated fiber is obtained by adding the reinforcing agent and the compound nucleating agent into the degraded pure monomer and carrying out polycondensation, so that the molecular weight of the regenerated fiber is effectively improved, the intrinsic viscosity of the regenerated fiber is higher, the thermal property and the flame retardant property are optimal, and the regenerated polyester fiber prepared by the method has excellent wrinkle resistance, wear resistance, high temperature resistance and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste polyester regeneration, and in particular to a recycling process for spinning regenerated fibers from waste polyester textiles. Background Art

[0002] With the rapid development of the global textile industry, polyester textiles have been widely used in clothing, home furnishings, automobiles and other industries due to their good wear resistance, wrinkle resistance and dyeability. However, the widespread use of polyester textiles has also brought about a large number of waste textile problems. If these waste polyester textiles are not properly handled, they will not only occupy precious land resources, but also cause long-term harm to the environment and ecosystem. Because there are many types of waste textiles, most of them were physically incinerated in the early days. The smoke generated during incineration is highly polluting and harmful to the atmospheric environment and human body.

[0003] In the existing technology, with the continuous advancement of research, the high value-added chemical recycling technology of waste polyester textiles has been widely used. Recycling and processing of various types of waste textiles combined with physical technical means can effectively play the residual value of waste textiles;

[0004] At present, the chemical recycling of waste polyester textiles includes processes such as mechanical crushing, degradation and repolymerization. The crushed waste fiber textiles are fluffy and have a small bulk density. If they continue to be degraded and repolymerized, the utilization rate is extremely low, and it is difficult for the liquid degradation agent to effectively contact them in a short period of time, which affects the degradation and repolymerization reaction process. The resulting regenerated fibers have poor barrier properties, low heat resistance, and the melt strength and tensile properties need to be further improved.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a recycling process for spinning regenerated fibers from waste polyester textiles, which is used to solve the technical problem in the prior art that the bulk density, heat resistance and mechanical strength of fibers prepared by recycling and regenerating waste polyester need to be further improved.

[0007] The purpose of the present invention can be achieved by the following technical scheme: A recycling process for spinning regenerated fibers from waste polyester textiles, comprising the following steps:

[0008] S1, crushing waste polyester textiles to obtain waste polyester powder, and pretreating the waste polyester powder to obtain pretreated polyester powder;

[0009] S2, passing the pretreated polyester powder through a melt flow rate meter, extruding it in a semi-molten solid phase under strong mechanical external force conditions, cooling it, and pulverizing it to obtain a densified polyester powder;

[0010] S3, placing the densified polyester powder, small molecule diol and alcoholysis catalyst into a nitrogen-protected reactor and stirring, raising the temperature of the reactor to 255-265° C., keeping the temperature for 3-4 hours, and post-treating to obtain alcoholysis monomer;

[0011] The reaction mechanism of alcoholysis monomer is:

[0012] Under the action of the catalyst, the cleavage of the ester bonds within the densified polyester powder chain and the ester bonds at the chain ends begins. During the cleavage process, the carbonyl oxygen on the alcoholysis monomer chain interacts with the active site in the catalyst, resulting in the protonation of the carbonyl carbon. The protonated carbonyl carbon cation is more susceptible to the attack of the hydroxyl oxygen in the alcohol molecule. After the hydroxyl oxygen attacks the carbonyl carbon cation, a tetrahedral intermediate transition state is formed. As the reaction proceeds, the carbon-oxygen bond that interacts with the catalyst breaks, and the electrons on the oxygen atoms in the alcoholysis monomer chain are transferred to form a carbon-oxygen double bond. The alcoholysis monomer chain gradually breaks into oligomers. As the reaction proceeds, the oligomers will continue to undergo ester exchange reactions with the alcohol molecules to eventually generate ethylene glycol and alcoholysis monomers.

[0013] Metal sodium salt alcoholysis catalyst reaction mechanism:

[0014] The metal sodium salt activates the nucleophilic reaction by forming a metal alcoholate with ethylene glycol. The reaction is carried out in two steps. The first step is to form a metal alcoholate. The second step is that the metal alcoholate attacks the densified polyester powder macromolecule as a nucleophilic reagent. The reaction mechanism of the first step is similar to the unimolecular nucleophilic substitution reaction mechanism. The metal catalyst attacks the hydroxyl group in ethylene glycol. The oxygen atom on the hydroxyl group contains a shared electron pair and forms an unstable intermediate complex with the metal ion with an empty orbit. At the same time, the OH bond gradually extends, and the electron cloud between the hydrogen and oxygen bonds gradually deviates to the oxygen atom, so that the positive charge on the hydrogen atom and the negative charge on the oxygen atom gradually increase, and finally ethylene glycol first forms a metal alcoholate.

[0015] S4, adding alcoholysis monomer, reinforcing material and polycondensation catalyst into a reaction kettle and stirring, raising the temperature of the reaction kettle to 240-250° C., keeping the temperature for reaction for 1-1.5 hours, then raising the temperature of the reaction kettle to 270-280° C., keeping the temperature for reaction for 1-2 hours, and post-treating to obtain a modified alcoholysis monomer;

[0016] The synthetic reaction mechanism of modified pure solution monomer is:

[0017] Another carboxylic acid group located at the meta position on the benzene ring of isophthalic acid can enhance the activity of the carboxylic acid and the positive charge of the carbonyl carbon atom, making it easy to combine with the oxygen atom in the alcohol to complete the nucleophilic substitution reaction between the alcohol and the acid. The higher the content, the easier the copolyester esterification reaction is. The polycondensation reaction is achieved by chelating and coordinating dihydroxyethyl ester with the catalyst. Dihydroxyethyl ester is the ligand and the catalyst is the receptor. The larger the chain volume of the ligand, the greater the spatial tension, the more difficult it is to coordinate, and the more difficult the polycondensation reaction is. The symmetry of the isophthalic acid molecule is poor, which can destroy the regularity of the macromolecular structure of the alcoholysis monomer, thereby hindering the crystallization of the alcoholysis monomer and reducing the crystallization ability of the alcoholysis monomer; at the same time, it will also lower the melting point of the alcoholysis monomer and reduce the processing temperature of the alcoholysis monomer.

[0018] S5, adding the modified alcoholysis monomer and the compound nucleating agent into a twin-screw extruder, and melt-extrude the twin-screw extruder into a melt spinning machine, and melt-spinning to obtain regenerated fibers.

[0019] The reaction mechanism of regenerated fiber synthesis is:

[0020] The composite nucleating agent can react chemically with the modified alcoholysis monomer molecular chain at high temperature to play a chemical nucleation role. It can be dissolved in the modified alcoholysis monomer melt at high temperature and react with the modified alcoholysis monomer molecular chain segments. This reaction will cause the molecular chain to break and generate ionic chain end groups. Such ionic chain end groups gather together to form ion clusters due to the action of ionic bonds. These ion clusters will precipitate in the melt to form heterogeneous nucleating agents. The composite nucleating agent can gather in the high temperature zone to become the nucleus center of heterogeneous nucleation, thereby increasing the nucleation temperature and nucleation ability. On the other hand, due to the molecular chain breakage caused by the reaction, the low molecular weight modified alcoholysis monomer molecular chain is more active and easier to diffuse into the crystal lattice than long chain molecules, so the growth rate of the crystal nucleus is faster.

[0021] Furthermore, in step S1, the pretreatment method is: adding the waste polyester powder and liquid alkali into a reactor, raising the temperature of the reactor to 40-50°C, ultrasonically dispersing for 60-90 minutes, and post-treating to obtain the pretreated polyester powder.

[0022] Furthermore, in step S1, the ratio of waste polyester powder to liquid alkali is 100g:1000ml, and the liquid alkali is 15-25wt% sodium hydroxide; the post-treatment method is: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with hot water until it is neutral and then dried, and the filter cake is placed in a drying oven at a temperature of 80-90°C to obtain pretreated polyester powder.

[0023] Furthermore, in step S2, the temperature of the melt flow rate instrument is 230-240°C and the pressure is 0.2-0.3 MPa.

[0024] Furthermore, in step S3, the weight ratio of the densified polyester powder, the small molecule diol, and the alcoholysis catalyst is 100-200:600-1000:1-2, the small molecule diol is ethylene glycol, propylene glycol, butanediol, and the alcoholysis catalyst is one or more of zinc acetate, zinc acetate dihydrate, sodium acetate, and sodium carbonate.

[0025] Furthermore, in step S3, post-treatment includes: after the alcoholysis reaction is completed, adding excess hot distilled water to the reaction system and stirring it fully, hot-filtering the mixed solution, transferring the filtrate to an environment with a temperature of 5-6°C, crystallizing for 20-24h, filtering at low temperature, eluting to obtain an alcoholysis monomer; and subliming the alcoholysis monomer under reduced pressure at 1.33kPa and 130°C to obtain high-purity alcoholysis crystals of white solid powder.

[0026] Furthermore, in step S4, the weight ratio of alcoholysis monomer, reinforcing material and polycondensation catalyst is 1400-1900:100-600:1-2, the reinforcing material is isophthalic acid, the polycondensation catalyst is ethylene glycol antimony, and the pre-shrinkage reaction is under 1.33 kPa; the post-treatment includes: after the final shrinkage reaction is completed, nitrogen is filled, staying for 15 minutes, and the modified pure alcoholysis monomer is discharged, which is a white hard solid.

[0027] Furthermore, in step S5, the dosage ratio of the modified alcoholysis monomer and the compound nucleating agent is 60-100:1-5, and the compound nucleating agent is composed of sodium benzoate, sodium carboxylate of ethylene and methacrylic acid copolymer, and ethylene glycol glycidyl ether in a weight ratio of 25-50:25-75:25; the feeding rate of the twin-screw extruder is 8r / min, and the screw speed is 17r / min; the temperature of the melt spinning machine is 240-250°C, the reaction time is 10-20min, the stretching temperature is 75-120°C, and the stretching ratio is 70%-90%.

[0028] The present invention has the following beneficial effects:

[0029] 1. Semi-melt densification means semi-plasticizing fiber textiles by high-strength mechanical rolling under conditions below the melting point of fiber textiles to achieve the purpose of densification. The semi-melt extrusion densification method can effectively solve the problems of low bulk density of textiles and difficult alcoholysis and repolymerization operations without reducing the molecular weight of polyester textiles too much, thereby increasing the viscosity of the regenerated fiber. Compared with other densification processes, the regenerated fiber obtained by semi-melt densification has higher viscosity, narrower relative molecular weight distribution, lower terminal carboxyl and diethylene glycol content, and better thermal stability. It is a better densification method before chemical recycling of waste fiber textiles. The bulk density of waste fiber textiles treated by the above densification treatment can be increased by about 10 times, making the regenerated fiber have higher characteristic viscosity and best thermal and flame retardant properties.

[0030] 2. For the composite nucleation system, its purpose is to play a synergistic role in the cooling crystallization process through the combination of several nucleating agents with different properties, overcome the shortcomings of a single nucleation system, and further improve the crystallization ability of the regenerated fiber. The modified alcoholysis monomer, especially after adding the composite nucleation system, has greatly improved crystallization behavior, far exceeding that of pure alcoholysis monomer. The crystallization peak temperature moves to high temperature, the half-crystallization time is shortened, and the crystallization rate constant is increased, thereby improving the mechanical strength, stability, and high temperature resistance of the regenerated fiber material. DETAILED DESCRIPTION

[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The sodium carboxylate salt of the copolymer of ethylene and methacrylic acid in the present invention is selected from the trade name Surlyn of DuPont Company;

[0033] Example 1

[0034] This embodiment provides a recycling process for spinning recycled fibers from waste polyester textiles, comprising the following steps:

[0035] S1. Preparation of pre-treated powder

[0036] Crushing waste polyester textiles to obtain waste polyester powder;

[0037] Weigh: 100 g of waste polyester powder and 1000 mL of sodium hydroxide solution are added to the reactor, the temperature of the reactor is raised to 40°C, and ultrasonic dispersion is performed for 60 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with hot water until neutral and then dried, and the filter cake is placed in a drying oven at 80°C to obtain pretreated polyester powder.

[0038] S2. Preparation of densified polyester powder

[0039] The pretreated polyester powder was passed through a melt flow rate meter and extruded in a semi-molten solid phase under strong mechanical external force conditions of a temperature of 230°C and a pressure of 0.2 MPa, and then cooled and crushed to obtain a densified polyester powder.

[0040] S3. Preparation of alcoholysis monomer

[0041] Weigh: 600 mL of ethylene glycol, 1 g of sodium carbonate and 100 g of densified polyester powder, add them into a reactor protected by nitrogen and stir, raise the temperature of the reactor to 255°C, and keep the reaction warm for 3 hours to obtain an alcoholysis monomer; after the alcoholysis reaction is completed, add excess hot distilled water into the reaction system and stir it thoroughly, filter the mixed solution by hot extraction, transfer the filtrate to an environment with a temperature of 5°C, crystallize for 20 hours, filter at low temperature, and rinse to obtain an alcoholysis monomer; sublimate the alcoholysis monomer under reduced pressure at 1.33 kPa and 130°C to obtain high-purity alcoholysis crystals of white solid powder.

[0042] S4. Preparation of modified alcoholysis monomer

[0043] Weigh: 1400g of alcoholysis monomer, 100g of isophthalic acid, and 1g of ethylene glycol antimony, add into the reactor and stir. Under the condition of 1.33kPa, the temperature of the reactor is raised to 240°C, and the reaction is kept warm for 1h for pre-shrinkage. The temperature of the reactor is then raised to 270°C, and the reaction is kept warm for 1h for final shrinkage. After the final shrinkage reaction is completed, nitrogen is filled and kept for 15 minutes. The modified alcoholysis monomer is discharged as a white hard solid.

[0044] S5. Preparation of regenerated fiber

[0045] Mixing sodium benzoate, sodium carboxylate of ethylene and methacrylic acid copolymer, and polyethylene glycol glycidyl ether in a weight ratio of 25:25:25 to obtain a composite nucleating agent;

[0046] Weigh: 1 g of the composite nucleating agent and 100 g of the modified alcoholysis monomer and add them into a twin-screw extruder; melt-extrude them into a melt spinning machine through the twin-screw extruder, and melt-spin to obtain regenerated fibers; wherein the feeding rate is 8 r / min, the screw speed is 17 r / min, the melt spinning machine temperature is 240°C, the reaction time is 10 min, the stretching temperature is 75°C, and the stretching ratio is 70%.

[0047] Example 2

[0048] This embodiment provides a recycling process for spinning recycled fibers from waste polyester textiles, comprising the following steps:

[0049] S1. Preparation of pre-treated powder

[0050] Crushing waste polyester textiles to obtain waste polyester powder;

[0051] Weigh: 100g of waste polyester powder and 1000ml of sodium hydroxide are added to the reactor, the temperature of the reactor is raised to 45°C, and ultrasonic dispersion is performed for 75 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with hot water until neutral and then dried, and the filter cake is placed in a drying oven at 85°C to obtain pretreated polyester powder.

[0052] S2. Preparation of densified polyester powder

[0053] The pretreated polyester powder was passed through a melt flow rate meter and extruded in a semi-molten solid phase under strong mechanical external force conditions of a temperature of 235°C and a pressure of 0.2 MPa, and then cooled and crushed to obtain a densified polyester powder.

[0054] S3. Preparation of alcoholysis monomer

[0055] Weigh: 150 mL of ethylene glycol, 1.5 g of sodium carbonate and 800 g of densified polyester powder are added to a reactor protected by nitrogen and stirred. The temperature of the reactor is raised to 260°C and the reaction is kept warm for 3.5 hours to obtain an alcoholysis monomer. After the alcoholysis reaction is completed, add excess hot distilled water to the reaction system and stir it thoroughly. The mixed solution is hot-filtered and the filtrate is transferred to an environment with a temperature of 5.5°C. Crystallization is carried out for 22.5 hours, low-temperature filtration is performed, and elution is performed to obtain an alcoholysis monomer. The alcoholysis monomer is sublimated under reduced pressure at 1.33 kPa and 130°C to obtain high-purity alcoholysis crystals of white solid powder.

[0056] S4. Preparation of modified alcoholysis monomer: 1650 g alcoholysis monomer, 350 g isophthalic acid and 1.5 g antimony glycol were weighed and added into a reactor with stirring. Under 1.33 kPa, the temperature of the reactor was raised to 245°C and the reaction was kept warm for 1.25 h for pre-shrinkage. The temperature of the reactor was then raised to 275°C and the reaction was kept warm for 1.5 h for final shrinkage. After the final shrinkage was completed, nitrogen was charged and the reaction was allowed to stand for 15 minutes. The modified alcoholysis monomer was discharged as a white hard solid.

[0057] S5. Preparation of regenerated fiber

[0058] Mixing sodium benzoate, sodium carboxylate of ethylene and methacrylic acid copolymer, and polyethylene glycol glycidyl ether in a weight ratio of 35:45:25 to obtain a composite nucleating agent;

[0059] Weigh: 3g of compound nucleating agent and 350g of modified alcoholysis monomer and add them into a twin-screw extruder; melt extrude them into a melt spinning machine through the twin-screw extruder, and melt spin them to obtain regenerated fibers; wherein the feeding rate is 8r / min, the screw speed is 17r / min; the temperature of the melt spinning machine is 245°C, the reaction time is 15min, the stretching temperature is 100°C, and the stretching ratio is 80%.

[0060] Example 3

[0061] This embodiment provides a recycling process for spinning recycled fibers from waste polyester textiles, comprising the following steps:

[0062] S1. Preparation of pre-treated powder

[0063] Crushing waste polyester textiles to obtain waste polyester powder;

[0064] Weigh: 100 g of waste polyester powder and 1000 mL of sodium hydroxide are added to the reactor, the temperature of the reactor is raised to 50°C, and ultrasonic dispersion is performed for 90 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with hot water until neutral and then dried, and the filter cake is placed in a drying oven at 90°C to obtain pretreated polyester powder.

[0065] S2. Preparation of densified polyester powder

[0066] The pretreated polyester powder was passed through a melt flow rate meter and extruded in a semi-molten solid phase under strong mechanical external force conditions of a temperature of 240°C and a pressure of 0.3 MPa, and then cooled and crushed to obtain a densified polyester powder.

[0067] S3. Preparation of alcoholysis monomer

[0068] Weigh: 1000 mL of ethylene glycol, 2 g of sodium carbonate and 200 g of densified polyester powder, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 265°C, and keep the reaction warm for 4 hours to obtain an alcoholysis monomer; after the alcoholysis reaction is completed, add excess hot distilled water into the reaction system and stir thoroughly, filter the mixed solution by hot extraction, transfer the filtrate to an environment with a temperature of 6°C, crystallize for 24 hours, filter at low temperature, and rinse to obtain an alcoholysis monomer; sublimate the alcoholysis monomer under reduced pressure at 1.33 kPa and 130°C to obtain high-purity alcoholysis crystals of white solid powder.

[0069] S4. Preparation of modified alcoholysis monomer

[0070] Weigh: 1900g of alcoholysis monomer, 600g of isophthalic acid, and 2g of ethylene glycol antimony, add into the reactor and stir. Under 1.33kPa, the temperature of the reactor is raised to 250°C, and the reaction is kept warm for 1.5h for pre-shrinkage. The temperature of the reactor is then raised to 280°C, and the reaction is kept warm for h for final shrinkage. After the final shrinkage reaction is completed, nitrogen is filled and kept for 15 minutes. The modified alcoholysis monomer is discharged as a white hard solid.

[0071] S5. Preparation of regenerated fiber

[0072] Mixing sodium benzoate, sodium carboxylate of ethylene and methacrylic acid copolymer, and polyethylene glycol glycidyl ether in a weight ratio of 50:75:25 to obtain a composite nucleating agent;

[0073] Weigh: 5 g of the composite nucleating agent and 600 g of the modified alcoholysis monomer and add them into a twin-screw extruder; melt-extrude them into a melt spinning machine through the twin-screw extruder, and melt-spin to obtain regenerated fibers; wherein the feeding rate is 8 r / min, the screw speed is 17 r / min, the melt spinning machine temperature is 250°C, the reaction time is 20 min, the stretching temperature is 120°C, and the stretching ratio is 90%.

[0074] Comparative Example 1

[0075] The difference between this comparative example and Example 3 is that in step S2, the temperature of the melt flow rate meter is set to 260°C.

[0076] Comparative Example 2

[0077] The difference between this comparative example and Example 3 is that in step S4, isophthalic acid is not added.

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 3 is that in step S3, sodium carbonate is replaced by an equal amount of tin acetate.

[0080] Comparative Example 4

[0081] The difference between this comparative example and Example 3 is that in step S5, the compound nucleating agent is replaced by an equal amount of sodium benzoate.

[0082] Product performance test:

[0083] Viscosity measurement: Weigh equal amounts of the waste polyester textile slices prepared in Examples 1-3 and the regenerated fiber slices prepared by the waste polyester recycling process, and record them as Examples 1-3 and Comparative Example, respectively; then dissolve the above samples in phenol / 1,1,2,2-tetrachloroethane (mass ratio 50 / 50), and prepare them into 0.5% solutions, test them at (25±1)°C using an Ubbelohde viscometer, and calculate the intrinsic viscosity using the Solomon-Ciuta equation; Calculation of molar mass: Using the Mark-Houwink equation, [η]=KMvα, K=7.44×10-4dL / g at 25°C, α=0.648, the test data obtained are recorded in Table 1:

[0084] The flame retardant properties and mechanical properties of the recycled fibers of Examples 1-3 and Comparative Examples 1-4 were tested, wherein the flame retardant properties and mechanical properties of the DTY polyester yarn were measured according to the standard FZ / T54085-2016 "Flame Retardant Polyester Low Elastic Yarn". The specific test results of the breaking strength and breaking elongation of the samples are shown in Table 1:

[0085] Table 1-Performance test data of samples

[0086]

[0087] Data Analysis:

[0088] It can be seen from the relevant data in Table 1 that, compared with the comparative example, when the waste polyester textiles are recycled by the process provided by the present invention, not only the molecular weight of the polyester polyester melt is increased, so that the regenerated fiber has a higher intrinsic viscosity, the best thermal properties and flame retardant properties, but also the obtained regenerated polyester fiber can have excellent wrinkle resistance, wear resistance, high temperature resistance and stability.

[0089] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0090] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0091] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A recycling process for spinning regenerated fibers from waste polyester textiles, characterized in that: The following steps are involved: S1, crushing waste polyester textiles to obtain waste polyester powder, and pretreating the waste polyester powder to obtain pretreated polyester powder; S2, pre-treated polyester powder is extruded in a semi-molten solid phase densification state under strong mechanical external force conditions through a melt flow rate meter, and then cooled and crushed to obtain densified polyester powder; S3, placing the densified polyester powder, small molecule diol and alcoholysis catalyst into a nitrogen-protected reactor and stirring, raising the temperature of the reactor to 255-265° C., keeping the temperature for 3-4 hours, and post-treating to obtain alcoholysis monomer; S4, adding alcoholysis monomer, reinforcing material and polycondensation catalyst into a reaction kettle and stirring, raising the temperature of the reaction kettle to 240-250° C., keeping the temperature for reaction for 1-1.5 hours, then raising the temperature of the reaction kettle to 270-280° C., keeping the temperature for reaction for 1-2 hours, and post-treating to obtain a modified alcoholysis monomer; S5, adding the modified alcoholysis monomer and the compound nucleating agent into a twin-screw extruder, and melt-extrude the twin-screw extruder into a melt spinning machine, and melt-spinning to obtain regenerated fibers.

2. The recycling process of regenerated fibers from waste polyester textiles according to claim 1, characterized in that: In step S1, the pretreatment method is: adding waste polyester powder and liquid alkali into a reactor, raising the temperature of the reactor to 40-50°C, ultrasonically dispersing for 60-90 minutes, and post-treating to obtain pretreated polyester powder.

3. The recycling process of regenerated fibers from waste polyester textiles according to claim 2, characterized in that: The ratio of the waste polyester powder to the liquid alkali is 100g:1000mL, and the liquid alkali is 15-25wt% of sodium hydroxide; the post-treatment method is: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the filter is filtered, the filter cake is washed with hot water until it is neutral and then dried, and the filter cake is placed in a drying oven with a temperature of 80-90°C to obtain the pretreated polyester powder.

4. The recycling process of regenerated fibers from waste polyester textiles according to claim 1, characterized in that: In step S2, the temperature of the melt flow rate meter is 230-240°C, and the extrusion pressure is 0.2-0.3 MPa.

5. The recycling process of regenerated fibers from waste polyester textiles according to claim 1, characterized in that: In step S3, the weight ratio of the densified polyester powder, small molecule diol and alcoholysis catalyst is 100-200:600-1000:1-2, the small molecule diol is ethylene glycol or methanol, and the alcoholysis catalyst is one or more of zinc acetate, zinc acetate dihydrate, sodium acetate and sodium carbonate.

6. The recycling process of regenerated fibers from waste polyester textiles according to claim 1, characterized in that: In step S3, post-treatment includes: after the alcoholysis reaction is completed, adding excess hot distilled water to the reaction system and stirring it fully, filtering the mixed solution while hot, transferring the filtrate to an environment with a temperature of 5-6°C, crystallizing for 20-24h, filtering at low temperature, eluting to obtain an alcoholysis monomer; and subliming the alcoholysis monomer under reduced pressure at 1.33kPa and 130°C to obtain high-purity alcoholysis crystals of white solid powder.

7. The recycling process of regenerated fibers from waste polyester textiles according to claim 1, characterized in that: In step S4, the weight ratio of the alcoholysis monomer, the reinforcing material, and the polycondensation catalyst is 1400-1900:100-600:1-2, the reinforcing material is isophthalic acid, the polycondensation catalyst is ethylene glycol antimony, and the pre-shrinkage reaction is under 1.33 kPa; the post-treatment includes: after the final shrinkage reaction is completed, nitrogen is filled, staying for 15 minutes, and the modified pure alcoholysis monomer is discharged, which is a white hard solid. The recycling process for regenerated fibers from waste polyester textiles according to claim 1 is characterized in that: In step S5, the modified pure monomer and the compound nucleating agent are used in a ratio of 100-600:1-5, and the compound nucleating agent is composed of sodium benzoate, sodium carboxylate of ethylene and methacrylic acid copolymer, and polyethylene glycol glycidyl ether in a weight ratio of 25-50:25-75:25; the feeding rate of the twin-screw extruder is 8r / min, and the screw speed is 17r / min; the temperature of the melt spinning machine is 240-250°C, the reaction time is 10-20min, the stretching temperature is 75-120°C, and the stretching ratio is 70%-90%.